71.3k views
1 vote
-2+2=−3(x−4) solve for x

User Ryangus
by
6.0k points

2 Answers

4 votes
X=4 answer

Explanation
User Hanky Panky
by
5.2k points
3 votes

♫ :::::::::::::::::::::::::::::: // Hello There ! // :::::::::::::::::::::::::::::: ♫

Expand the parenthesis:

-3(x - 4) --> -3x + 12

Now we have:

-3x + 12 = -2 + 2

Simplify to get:

-3x + 12 = 0

Subtract 12 from both sides:

-3x = -12

Divide both sides by -3:

x = 4

❄️

➶ Hope This Helps You!

➶ Good Luck (:

➶ Have A Great Day ^-^

ʜᴀɴɴᴀʜ

User Eder
by
5.0k points